Analysis of Parvovirus B19 persistence and reactivation in human heart layers - Badrinath, Ashwin; Gardere, Anais; Palermo, Samantha L.; Campbell, Kenneth S.; Kloc, Anna (Frontiers in Virology, 2024)
Heart disease is the leading cause of death worldwide. Myocarditis, or inflammation of the cardiac muscle, is estimated to cause up to 1.5 million cases annually, with viral infection being the most common disease culprit. Past studies have shown that Parvovirus B19 is routinely detected in endomyocardial biopsies. This virus has been linked to acute heart inflammation, which can cause cardiac muscle damage. However, because Parvovirus B19 can be found in the heart tissues in the absence of disease symptoms, it is unclear if the long-term presence of the virus contributes to, or initiates, heart disease. Here, we utilized a PCR-based detection assay to assess the presence of the B19V genome and its mRNA intermediates in human heart tissues. The analysis was carried out in three heart layers derived from one individual: epicardium, endocardium and myocardium. We showed the Parvovirus B19 genome presence variability in different heart layers. Similarly, viral transcriptional activity, assessed by the mRNA presence, was detected only in a few of the analyzed samples. Our results suggest that localized sites of Parvovirus B19 infections may exist within individual heart layers, which may have implications for the cardiac muscle inflammation.